APPRECIATING POSITIVITY OF COVID-19 - Joel Rey Ugsang Acob (Belitung Raya Foundation, Indonesia, 2020)
This article aims to decipher the effects of COVID-19 on humans, thus maintaining the equanimity of life. Ecclesiastes continually radiates its significance these trying times with the operation that everything has its season under heavens. Only an undesirable and existential peril like COVID-19 steered to such profound transformation vastly. The portrayal is considered some of the many obvious outgrowths of the COVID-19 plague. Compared to 2019, levels of pollution have significantly subtracted to 50% because of the measures to ensure the virus is contained. Recognizing health-wealth worth took place when the world watches someone busy picking up the pieces of their lives amidst helpless speculators. In the busyness of life, most, if not all, rarely spend time to slow down, stay home, and go inward. The pandemic teaches us lessons about relationships. The invisible lines that divide people into strata - religion, sex, age, and country have all disappeared as humanity is confronted with this menace as people.